2020
DOI: 10.1111/bjh.16950
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia is independently associated with poor outcome in patients hospitalized for COVID‐19

Abstract: Thrombocytopenia is independently associated with poor outcome in patients hospitalized for COVID-19 Thrombocytopenia (defined by platelet count <150 9 10 9 / l) has been observed in up to 36% of patients with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for coronavirus disease 2019 (COVID-19). 1 In this setting, thrombocytopenia is usually mild, caused by platelet activation and consumption. 2,3 In a recent paper published in the British Journal of Haematology, Jiang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 11 publications
6
44
0
2
Order By: Relevance
“…In a case series of patients admitted to an intensive care unit in Wuhan, a platelet count of <100 × 10 9 /L was observed in only 5% of patients 14 . Similar findings were reported in a French cohort study with mild thrombocytopenia identified in about a quarter of COVID‐19 patients on admission to hospital and this was independently predictive of the risk of admission to ICU, mechanical ventilation or death 19 . Furthermore, data from multiple studies suggest that anaemia is not a prominent feature of COVID‐19 even in severe cases 11,13,14 .…”
Section: Blood Count Abnormalitiessupporting
confidence: 81%
“…In a case series of patients admitted to an intensive care unit in Wuhan, a platelet count of <100 × 10 9 /L was observed in only 5% of patients 14 . Similar findings were reported in a French cohort study with mild thrombocytopenia identified in about a quarter of COVID‐19 patients on admission to hospital and this was independently predictive of the risk of admission to ICU, mechanical ventilation or death 19 . Furthermore, data from multiple studies suggest that anaemia is not a prominent feature of COVID‐19 even in severe cases 11,13,14 .…”
Section: Blood Count Abnormalitiessupporting
confidence: 81%
“…Although no specific pulmonary pathologic findings have been observed, thrombosis of major vessels and microcirculation are often highlighted. It is well-known that COVID-19 patients often show prothrombotic coagulation abnormalities [37][38][39], being thrombocytopenia associated with a poor clinical outcome [40]. In this autopsy study, we report that pulmonary MKs are a common finding in COVID-19 patients with pulmonary damage.…”
Section: Introductionmentioning
confidence: 64%
“…In agreement with recent reports, thrombocyte counts were lower in patients with COVID-19, and thrombocytopenia was associated with an increased risk of in-hospital mortality. 6,7 Lymphopenia, previously presented as a hallmark of COVID-19, 1,8,9 is a common feature of critical illness in general. 10 Indeed, in our present cohort, neither the median lymphocyte counts nor the prevalence of lymphopenia (<1Á0 9 10 9 /l) were different between the patients with COVID-19 and the controls.…”
Section: Resultsmentioning
confidence: 99%